2020
DOI: 10.18825/iremjournal.529056
|View full text |Cite
|
Sign up to set email alerts
|

DOĞRUDAN YABANCI YATIRIMCILARIN YER SEÇİMİ: GÜNCEL YABANCI ÇALIŞMALARDA ELE ALINAN FAKTÖRLER ve ANALİZLERDE KULLANILAN YÖNTEMLER ÜZERİNE KEŞİFSEL BİR ARAŞTIRMA

Abstract: Küreselleşen ekonomilerin en önemli getirilerinden biri de çokuluslu şirketler tarafından yapılan doğrudan yabancı yatırımların yolunu açmasıdır. Birçok gelişmekte olan ülke, doğrudan yabancı yatırım girişlerini, ekonomik kalkınma fırsatı için yeni bir kapı olarak görmektedir. Olaya doğrudan yabancı yatırımı gerçekleştirmek isteyen çokuluslu şirketler perspektifinden bakıldığında ise yer seçiminin stratejik önemi ortaya çıkmaktadır. Çalışmada, ev sahibi ülkenin yer seçim kararında etkili olan, doğrudan yabancı… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
(41 reference statements)
0
1
0
Order By: Relevance
“…Economics 46 Açıkalın et al, 2009;Bağcı, 2013;Bayır, 2019;Bayır, 2020;Bülbül, 2016;Çinko, 2009;Demirel, 2006;Doğan 2014;Erdoğan 2011;Gerçeker, 2010;Hoca, 2008;Kızılca, 2007;Özel, 2018;Selek, 2009;Tarı ve Bıdırlı, 2009;Tüzün, 2019;Tunca, 2005;Uzgören ve Akalın, 2016; Business Administration 39 Algan, 2006;Altuntaş et al, 2015;Baykal, 2013;Çelik et al, 2015;Erdem, 2019;Ergün 2007;Eryiğit, 2010;Gürman, 2006;Karadağ, 2018;Külünk, 2019;Mert, 2012;Mıhoğlu, 2019;Nas et al, 2020;Öz, 2020;Rabenirina, 2013;Rüstemli, 2008;Seyidov, 2009;Sezgin, 2019;Şirin, 2019;Türken, 2018;Yalçın, 2011; According to Table 2, it has been observed that most studies have been conducted in the field of Economics and Business Administration. Other areas that publications focus are Banking, International Business, Finance, Labor Economics and Industrial Relations, Geography and Industrial Engineering.…”
Section: Field Of Study Articles and Thesis Referencesmentioning
confidence: 99%
“…Economics 46 Açıkalın et al, 2009;Bağcı, 2013;Bayır, 2019;Bayır, 2020;Bülbül, 2016;Çinko, 2009;Demirel, 2006;Doğan 2014;Erdoğan 2011;Gerçeker, 2010;Hoca, 2008;Kızılca, 2007;Özel, 2018;Selek, 2009;Tarı ve Bıdırlı, 2009;Tüzün, 2019;Tunca, 2005;Uzgören ve Akalın, 2016; Business Administration 39 Algan, 2006;Altuntaş et al, 2015;Baykal, 2013;Çelik et al, 2015;Erdem, 2019;Ergün 2007;Eryiğit, 2010;Gürman, 2006;Karadağ, 2018;Külünk, 2019;Mert, 2012;Mıhoğlu, 2019;Nas et al, 2020;Öz, 2020;Rabenirina, 2013;Rüstemli, 2008;Seyidov, 2009;Sezgin, 2019;Şirin, 2019;Türken, 2018;Yalçın, 2011; According to Table 2, it has been observed that most studies have been conducted in the field of Economics and Business Administration. Other areas that publications focus are Banking, International Business, Finance, Labor Economics and Industrial Relations, Geography and Industrial Engineering.…”
Section: Field Of Study Articles and Thesis Referencesmentioning
confidence: 99%